THE EXISTENCE OF MDTA AL WASHLIYAH AS A RELIGIOUS INFORMATION LITERACY AGENT IN THE MEDAN AREA URBAN AREA - Rayhan, Muhammad; Arsyad, Junaidi; Sumanti, Solihah Titin (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2025)
This study explores the institutional role of Madrasah Diniyah Takmiliyah Awaliyah (MDTA) Al Washliyah in promoting religious information literacy among urban Muslim youth in Medan, Indonesia. Contrary to the common perception of madrasahs as merely spaces for rote Qur'anic learning, MDTA Al Washliyah actively integrates media analysis and critical religious interpretation into its pedagogy. Using a qualitative method combining in-depth interviews and classroom observations, and employing snowball sampling to identify key informants, the research found that teachers encourage students to question, verify, and contextualize online Islamic content. These practices align with UNESCO’s Media and Information Literacy (MIL) framework and reflect the Islamic tradition of tafaqquh fi al-din—a deep, contextualized understanding of religion. Despite these innovations, the study also identifies critical challenges. Teachers face limited digital training, poor infrastructure, and minimal institutional support. Moreover, a cultural and generational gap exists between digitally-native students and digitally-limited educators. Parental involvement remains low, as many guardians view MDTA narrowly as a place for Qur’anic recitation, limiting support for media literacy initiatives. Nevertheless, the findings suggest that MDTA Al Washliyah, as a community-rooted institution, holds significant potential as a literacy agent. Through its culturally embedded and dialogic pedagogy, it fosters ethical digital citizenship and resilience against misinformation. In conclusion, MDTA Al Washliyah exemplifies how grassroots religious schools can adapt to digital realities, provided they receive adequate training, technological support, and broader cultural alignment. This study contributes to the discourse on integrating media literacy within Islamic education in the context of Indonesia’s urban society.